x(2)=-4x-3

Simple and best practice solution for x(2)=-4x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(2)=-4x-3 equation:


Simplifying
x(2) = -4x + -3

Reorder the terms for easier multiplication:
2x = -4x + -3

Reorder the terms:
2x = -3 + -4x

Solving
2x = -3 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
2x + 4x = -3 + -4x + 4x

Combine like terms: 2x + 4x = 6x
6x = -3 + -4x + 4x

Combine like terms: -4x + 4x = 0
6x = -3 + 0
6x = -3

Divide each side by '6'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| 0.33333333333333x-2=-0.5x+3 | | 5+7n=-3 | | x^3+5x^2-7x=4 | | 0.5x-3=-0.33333333333333x+2 | | -15+8=x | | x^3+5x^2-7x-4=0 | | 35m^6p^2/5m^10p | | m(2)-40=-3m | | 2x^3-14x^2-16x=0 | | 2(1/2+1/5)+2 | | 16+2y=-6y | | 6x+8=9+10 | | 4x+1/3=3x-1/2 | | -30x^2-53x-21=0 | | (-3+x-x)(-2)= | | 2(6-t)=15(2t) | | 4x+1*4x+1= | | 4/3*9/8/9/4 | | 0.5x-0.125=-0.33333333333333x+0.25 | | 6x-23=17-6(5-2x) | | (4x^3y^5)= | | 2x+y+z=3 | | 34x-10x=360x | | 2(x-2)+4=10x | | 0.5x-0.125=0.33333333333333x+0.25 | | x^2+4x+27=-8x-5 | | 3r(2)-21=-18r | | 8x+12-5x=21 | | k(2)-3k-18=0 | | 9-5x+1=15 | | 8/3x-2(x+3)=14/3x-10 | | 11x+8=(x+2)(3x+4) |

Equations solver categories